Multi-Omics Analysis Reveals the Dynamic Changes of RNA N6-Methyladenosine in Pear (Pyrus bretschneideri) Defense Responses to Erwinia amylovora Pathogen Infection - Han, Chenyang; Zhang, Feng; Qiao, Xin; Zhao, Yancun; Qiao, Qinhai; Huang, Xiaosan; Zhang, Shaoling (Frontiers in Microbiology, 2022)
N6-methylated adenine (m6A) is the most prevalent modification of mRNA methylation and can regulate many biological processes in plants, such as mRNA processing, development, and stress response. Some studies have increased our understanding of its various roles in model plants in recent years. Nevertheless, the distribution of m6A and the impact of m6A on the regulation of plant defense responses against pathogen inoculation are virtually unknown in pear. In this study, MeRIP-seq and RNA-seq data from healthy and inoculated plants were analyzed to assess the changes in the transcript levels and posttranscriptional modification of pear in response to the fire blight pathogen Erwinia amylovora. Following the analysis of 97,261 m6A peaks, we found that m6A preferred to modify duplicate genes rather than singleton genes and that m6A-methylated genes underwent stronger purifying selection. A total of 2,935 specific m6A sites were detected at the transcriptome level after inoculation, which may increase defense-related transcript abundance to enhance pear resistance. In addition, 1,850 transcripts were detected only in the mock-inoculated groups. The hypomethylated transcripts were mainly related to transcriptional regulation and various biological processes, such as chloroplast organization and sucrose biosynthetic processes. In addition, we found that the extent of m6A methylation was significantly positively correlated with the transcript level, suggesting a regulatory role for m6A in the plant response.